Material factors of human lifespan from the perspective of Islamic teaching - Ziaodin Olianasab; Ali Akbar Hazeri Geqeh; Amaneh Rameparvar; Amir Mohammad Mortazavian (Shahid Beheshti University of Medical Sciences, 2016)
For downloading the full-text of this article please click here. Having long life and spend it in obedience to God from the perspective of Islamic teaching has introduced as a sign of prosperity and happiness. Although now a day proponents of long life pay more attention to researches of scientists, this article has explained the material factors of human long life from the Islamic perspective. God determines human lifespan but has given them opportunity to play the role in their life and accordance with the will of Almighty God, their life can be short or long. Human role in his life is to do things, live in a certain and normal life and die soon or late. However the effective factors on Reductions and increase of human life can be studied according to Islamic perspective (material and spiritual factors). This research reviewed the Material and spiritual factors affecting the longevity and by introducing fifteen material factors which increase human life span from the perspective of verses and Hadiths finally concluded many experimental factors increasing longevity were consistent with these factors. In a few cases, the vision outlined in Hadiths has raised new topics for research of medical scientist.  Keywords:Human Life, Factors of life span, survival, Signs and miracles For downloading the full-text of this article please click here.